An Investigation into Persian Language Teachers’ Attitude toward Oral Corrective Feedback in Classroom - Amir Zand-Moghadam; Faranak Eslami (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Given the important role of oral corrective feedback (OCF) in developing language learning and due to the fact that no study has ever investigated Persian language teachers’ attitude toward providing oral corrective feedback, the purpose of the present study was to investigate and critically analyze the attitude and performance of Persian language teachers while providing OCF. To this end, 15 Persian language teachers were selected and given a questionnaire to complete. The questionnaire included both 5-point Likert scale and open-ended items. The findings revealed that Persian language teachers had a positive attitude toward OCF and that elicitation feedback was the most frequently used type of OCF, while repetition, clarification request and metalinguistic feedback were observed to be the least frequently used type of feedback. It can be concluded that Persian language teachers’ positive attitude toward OCF resulted in the effective use of feedback in the process of Persian language teaching. It can also be claimed that Persian language teachers made use of a variety of feedback types; the most frequent of all was elicitation feedback. The findings of this study have implications for Persian language teachers, researchers, and teacher educators.